According Due Credit to Creditors’ Interests: Examining Directorial Duties in Near Insolvency and Insolvency Scenarios - L Viswanathan; Animesh Bisht; Karan Sangani (Vikalpa)
Two recent developments in the United Kingdom and Ireland have reignited the debate regarding the scope of the directors’ fiduciary duties during financial distress when the creditors’ economic interests in the company’s assets assume greater significance. This paper examines these developments and discusses the reorientation of the directors’ fiduciary duties that is necessary in near insolvency and insolvency scenarios from shareholder interest primacy to safeguarding the creditors’ interests. This paper further discusses the implications and workability of such position in the Indian context to examine how the directors’ fiduciary duties towards creditors can be formalised under the Indian regime.